RANCANG BANGUN APLIKASI GATTO FRIENDS DENGAN METODE PROFILE MATCHING BERBASIS ANDROID (STUDI KASUS UNDIP CAT LOVERS SEMARANG): Humam Alif Subhi, Yasni Djamain, M.Farid Rifai - Jurnal, Redaksi Tim (PETIR, 2018)
The aim of this research is to design the cat couple search application according to Veterinarian procedure and association of cats association. The method of decision support system used is Profile Matching with the process of comparing the individual competencies into the group's competence so as to know the difference of competence, Software Development Method used is Luther Multimedia Method and Application Design using Unified Modeling Language. Cat’s data used for research application that is in UNDIP cat lovers community by using Black Box method test. It is hoped that the results of this study show that cat search apps can help cat lovers find mating partners for pet cats that have a match with pet and pet owners and interact with other pet owners around the more efficient, fast and computerized.